Recent advances in understanding catalysis of protein folding by molecular chaperones - Balchin, David; Hayer‐Hartl, Manajit; Hartl, F. Ulrich (FEBS letters, 2020)
Molecular chaperones are highly conserved proteins that promote proper folding of other proteins in vivo. Diverse chaperone systems assist de novo protein folding and trafficking, the assembly of oligomeric complexes, and recovery from stress‐induced unfolding. A fundamental function of molecular chaperones is to inhibit unproductive protein interactions by recognizing and protecting hydrophobic surfaces that are exposed during folding or following proteotoxic stress. Beyond this basic principle, it is now clear that chaperones can also actively and specifically accelerate folding reactions in an ATP‐dependent manner. We focus on the bacterial Hsp70 and chaperonin systems as paradigms, and review recent work that has advanced our understanding of how these chaperones act as catalysts of protein folding.